Experimental Study of the Influence of Silica Fume on the Properties of Mortar - LIANG Rongchuang; SUN Haiyan; DONG Xinyue; ZHAO Yang; GE Yunlong (Renmin Zhujiang)
To study the effects of silica fume on the mechanical properties and drying shrinkage properties of cement mortar,we investigated the effects of silica fume content on the fluidity,compressive strength,flexural strength,and drying shrinkage rate of cement mortar under different water-binder ratios.The test results show that the jumping table fluidity of cement mortar under the two water-binder ratios follows the same change trend,that is,to decrease as the silica fume content increases.The incorporation of silica fume improves the strength of cement mortar of different water-binder ratios.Under a water-binder ratio of 0.40,a10% silica fume increases the compressive and flexural strengths of cement mortar at 28 d by17.7% and11.0% respectively compared with those of the benchmark group.When the water-binder ratio is 0.45,the corresponding values are 21% and12% respectively.The incorporation of silica fume also increases the drying shrinkage rate of the mortar in both cases,and the rate grows with the silica fume content.The drying shrinkage rate is larger when the water-binder ratio is 0.40.When the water-binder ratio is 0.45,the improvement of the drying shrinkage rate at 60 d is more obvious compared with that of the benchmark group.